Aquaporin-4： orthogonal array assembly, CNS functions, and role in neuromyelitis optica - Verkman, Alan S; Ratelade, Julien; Rossi, Andrea; Zhang, Hua; Tradtrantip, Lukmanee (Acta pharmacologica Sinica, 2011)
Aquaporin-4 （AQP4） is a water-selective transporter expressed in astrocytes throughout the central nervous system, as well as in kidney, lung, stomach and skeletal muscle. The two AQP4 isoforms produced by alternative spicing, M1 and M23 AQP4, form heterotetramers that assemble in cell plasma membranes in supramolecular structures called orthogonal arrays of particles （OAPs）. Phenotype analysis of AQP4-null mice indicates the involvement of AQP4 in brain and spinal cord water balance, astrocyte migration, neural signal transduction and neuroinflammation. AQP4-nuil mice manifest reduced brain swelling in cytotoxic cerebral edema, but increased brain swelling in vasogenic edema and hydrocephalus. AQP4 deficiency also increases seizure duration, impairs glial scarring, and reduces the severity of autoimmune neuroinflammation. Each of these phenotypes is likely explicable on the basis of reduced astrocyte water permeability in AQP4 deficiency. AQP4 is also involved in the neuroinflammatory demyelinating disease neuromyelitis optica （NMO）, where autoantibodies （NMO-IgG） targeting AQP4 produce astrocyte damage and inflammation. Mice administered NMO-IgG and human complement by intracerebral injection develop characteristic NMO lesions with neuroinflammation, demyelination, perivascular complement deposition and loss of glial fibrillary acidic protein and AQP4 immunoreactivity. Our findings suggest the potential utility of AQP4-based therapeutics, including small-molecule modulators of AQP4 water transport function for therapy of brain swelling, injury and epilepsy, as well as small-molecule or monoclonal antibody blockers of NMO-IgG binding to AQP4 for therapy of NMO.